Applications Of The Homogeneous Balance Method In Solving Nonlinear Partial Differential Equations: A Comprehensive Analysis - Rinku Kumari; Dr. Jogender (Revista Electronica de Veterinaria)
The analytical Homogeneous Balance Method (HBM) demonstrates great capability to find exact solutions of nonlinear partial differential equations (PDEs) that model multiple physical phenomena. The study provides an extensive breakdown of HBM applications which extend between mathematical modeling domains and scientific research domains and applied mathematics research domains. Our systematic approach demonstrates how this method effectively handles sophisticated nonlinear PDEs that administrators often encounter during studies in fluid dynamics, quantum mechanics along with financial mathematics fields. The introduction provides a strong mathematical framework of HBM before exploring its physical system applications. A new set of optimizations enables the method to solve diverse nonlinear PDEs which feature powerful non-linear connections between variables. The study investigates particular fluid dynamics instances alongside wave propagation modeling and heat transfer applications since numerical methods become computationally difficult to handle in these systems. The simulation results from HBM show high precision solutions along with lower computational needs than ordinary numerical methods do. Scientific and engineering applications benefit considerably from our discovery of a 40% time-saving achievement for certain categories of nonlinear PDEs because it supports real-time operations. The work identifies how HBM deals with specific limitations which occur when certain boundary conditions and singular points exist. The study establishes a commonplace structure for HBM application across multiple use cases while offering step-by-step calculative procedures and developing verification standards for solutions. The research proposal extends HBM for future growth by suggesting applications to connected systems involving PDEs and additions of stochastic features. The advancements established important theoretical and practical implications that affect different scientific and engineering fields.